STUDI DAMPAK PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) TERHADAP TINGKAT PERTUMBUHAN ANAK USIA 5 BULAN - Vita Kartika; Abas B. Jahari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2003)
STUDY ON THE EFFECT OF THE SUPPLEMENTARY FEEDING ON THE GROWTH RATE OF 5 MONTH OLD INFANT AT THE BOGOR REGENCYBackground: Growth faltering of infants In Indonesia started at their early life i.e 1-3 month of their age. Growth faltering appear mainly due to the supplementary feeding practice which is not adequate for their requirement. Objectives: The objectives of this research are to evaluate the effect of food supplementation which made by industry. The food contains allmicronutrient as well as macronutrients that are needed for the growth of 5 month infant. Methods: Research design is quasi experimental. Data analysis were used univariat, bivariat, multivariat analysis (linear regression) to find out independent variable which most influenced to the weight increase of the sample. Sample population are infants 5 month old from the poor families at Kemang and Ciomas district which fulfill the inclusion of criteria. The treatment group (53 samples) received intervention in form of supplementary food made by industry containing energy 197 kcal and 4,8 gram protein, given 48 gram/day for 4 months period, on the other hand the control group (51 samples) did not receive food intervention. The foods were distributed weekly. Data collection (anthropometries measurement) of infant every months during 4 months period of this research. Results: After 4 months intervention, the weight of treatment group has higher increase  than the control group which is 1,30 kg for the treatment group and 0,52 kg for the control group. Growth rate during 4 months period can be seen from the z score point according to weight for age and weight for length indexes. Z score showed significant difference (p<0,005) between the two groups. At treatment group although the growth rate tend to decrease it was stil on the normal rate while in the control group the growth development were sharply decrease below the normal weight (<2 SD).Conclusions: Intervention by formulated supplementary food made by industry increased body weight significally. Intervention improved the intake of energy, protein and iron and decreased the morbidity rate significally. Keywords: growth rate, supplementary food and morbidity.